Hypo-osmotic stimulation of active Na+ transport in frog muscle: apparent upregulation of Na+ pumps - Venosa, Roque Alberto (1991)
The purpose of this work was to determine if hypotonicity, in addition to the stimulation of active Na+ transport (Venosa, R.A., 1978, Biochim. Biophys. Acta 510:378-383), promoted changes in (i) active K+ influx, (ii) passive Na+ and K+ fluxes, and (iii) the number of 3H-ouabain binding sites. The results indicate that a reduction of external osmotic pressure (pi) to one-half of its normal value (pi = 0.5) produced the following effects: (i) an increase in active K+ influx on the order of 160%, (ii) a 20% reduction in Na+ influx and K+ permeability (PK), and (iii) a 40% increase in the apparent density of ouabain binding sites. These data suggest that the hypotonic stimulation of the Na+ pump is not caused by an increased leak of either Na+ (inward) or K+ (outward). It is unlikely that the stimulation of active Na+ extrusion and the rise in the apparent number of pump sites produced by hypotonicity were due to a reduction of the intracellular ionic strength. It appears that, at least in part, the stimulation of active Na+ transport takes place whenever muscles are transferred from one medium to another of lower tonicity even if neither one was hypotonic (for instance pi = 2 to pi = 1 transfer). Comparison of the present results with those previously reported indicate that in addition to the number of pump sites, the cycling rate of the pump is increased by hypotonicity. Active Na+ and K+ fluxes were not significantly altered by hypertonicity (pi = 2).